Dental caries in children and adolescents with poorly-controlled diabetes: a case-control study - ElBshari, Shahd; Afrooz, Imrana; Beck, Rasha Hassan; Watad, Rama; Al-Qahtani, Nabras; Deeb, Asma (Frontiers in Oral Health, 2024)
The relationship between diabetes and dental caries remains uncertain. The main objective of this study was to quantify dental caries in children and adolescents with and without poorly-controlled diabetes to examine whether poorly-controlled diabetes influences caries prevalence and severity. This was a case-control study of children and adolescents with poorly-controlled diabetes and age-matched controls attending paediatric clinics at Sheikh Shakhbout Medical City, Abu Dhabi, UAE in August 2022. Dental caries was diagnosed by visual examination and dental probing to derive total number of decayed, missing, and filled tooth or surface (DMFT/DMFS) indices. Differences in caries metrics between subjects with diabetes and controls were assessed using chi-squared or Mann Whitney U-tests. Fifty-seven children and adolescents without diabetes and 42 with poorly-controlled (HbA1c ≥ 7.5) diabetes were recruited. The median (interquartile range, IQR) DMFT index was 4 (5) and the DMFS index was 4 (11). There were no significant differences in DMFT % [14.0 (21.5) vs.13.0 (20.0); p = 0.602], DMFT index [4 (5) vs. 3 (6); p = 0.749], nor DMFS index [5 (12) vs. 4 (11); p = 0.484] between patients and controls. Diabetes either has no effect on caries risk or its effect is so small that it is masked by dominant risk factors such as diet and obesity that require addressing through robust public health measures. While poor glycaemic control does not appear to influence caries risk, diet and obesity remain serious and addressable risk factors affecting oral health.